Stem Cells in Dentistry: Knowledge among the Dental Practitioners of Nepal - Pandey, Nashib; Koju, Sushmit; Maharjan, Nisha; Chaudhary, Rajan; Chaulaagain, Rajib (Journal of Nepalese Society of Periodontology and Oral Implantology, 2023)
Introduction: Dentists are expected to play a major role in advancing the field of stem cell research as well as directing and implementing future stem cell therapies in dentistry. Accordingly, good basic knowledge and a positive attitude toward stem cells and their potential applications are essential among the dentists. Objective: This study aimed to assess the prevalence of knowledge on stem cell among the dental practitioners. Methods: A descriptive cross-sectional study was conducted among the registered dental practitioners in Nepal. An online questionnaire was created with the help of Google forms between 27 October, 2021 to 22 July, 2022 after receiving ethical approval from the Institutional Review Committee of a tertiary care center. The questionnaire was designed after reviewing pertinent literatures. Convenience sampling method was used. Data from Google forms were entered in Microsoft Excel version 2016 and were analysed with IBM SPSS v.20. Results: Among the total of 280 responses received, the prevalence of good knowledge about stem cells was found to be 53 (18.93%) (14.34- 23.52, 95% Confidence Interval). Majority of the respondents with good knowledge score were female 41 (77.36%). Almost all of the respondents knew about the term stem cells and its sources. But very few 68 (24.29%) of them knew about the availability of stem cell banks in Nepal. Conclusions: The prevalence of good knowledge about stem cell in dentistry was found to be less than half the sample size. Hence, there is a need to cover stem cells related information in dental curricula in Nepal.